Brain–Gut Axis and Gut Microbiota: Possible Role of Gut Microbiota in Childhood Mental Health and Diseases - Sudo, Nobuyuki (Journal of Pediatric Biochemistry, 2015)
The role of gut bacteria in human health and diseases has gained significant research interest. The human intestine is inhabited by more than 1,000 bacterial species and an estimated 1011 to 1012 bacterial cells are present per gram of feces. In addition to their well-established role in postnatal maturation of the mammalian immune system, gut bacteria are also responsible for an enormous array of metabolic activities that include the digestion of food and the production of a host of biologically active substances. Moreover, our previous study on gnotobiotic mice demonstrated that gut microbiota is an environmental determinant that regulates the development of the hypothalamic–pituitary–adrenal (HPA) axis stress response and behavioral phenotypes. In this review, we focus on the signaling pathway between the gut microbiota and the brain in terms of the effects of commensal microbiota on the HPA axis response and behavioral characters, and further consider the possible link between gut microbiota and childhood mental health.
Keywords: autism; behavior; gut microbiota; hypothalamic–pituitary–adrenal axis; stress